COLONIALITY AND ENVIRONMENTAL DEVASTATION IN IMBOLO MBUE’S HOW BEAUTIFUL WE WERE - Zareena Qasim; Munnzza Noreen; Muhammad Afzal (International Journal of Contemporary Issues in Social Sciences, 2024)
Colonization is the process by which a country establishes control over a foreign territory, often exploiting its resources and imposing its cultural, economic, and political systems. This process is a major factor contributing to ecological issues. Therefore, this research paper aims to reveal the destructive role of colonization on environmental stability and the social marginalization of locals in How Beautiful We Were by Mbue. As a piece of environmental fiction, How Beautiful We Were offers a depiction of ecological realism and explores the environmental devastation resulting from colonization. It illustrates how colonial forces, particularly oil corporations driven by development, pollute the land, exploit natural resources, harm the environment, and create economic inequalities, while marginalizing local cultures and societies. Western colonial corporations are identified as primary culprits of ecological damage and the social marginalization of the people in Africa. Employing a qualitative approach, this research paper analyzes and interprets data on the colonial impact on the environment and the social marginalization of the locals. Research findings indicate that colonial activities play a significant role in causing environmental concernsand the social marginalization of locals. This research paper is expected to be a significant addition to the field of postcolonial ecocriticism.